Pengaruh Latihan Kekuatan Arm Muscles dan Abdominal Muscles Terhadap Shooting Bola Tangan (Studi Pada Atlet Bola Tangan Bojonegoro) - Iwan Burhannudin Al-ayyubi; Roy Januardi Irawan (Indonesian Journal of Kinanthropology (IJOK), 2021)
Background: This study aims to determine the effect of abdominal muscle strength and arm muscles on shooting in Bojonegoro handball athletes. Methods: In this research the method used is descriptive quantitative. To find out the results of this shooting, it was measured using a standing shoot test instrument, while the abdominal muscles and arm muscles used sit-up and push-up instruments. Results: The results of this study indicate that handball shooting is influenced by many aspects, one of which is the strength of the arm muscles and abdominal muscles. Conclusions: Individually, arm muscle strength has the greatest influence on shooting variables performed in handball. In conclusion, the variable strength of the arm muscles and abdominal muscles greatly influences the shooting variable that is carried out in handball sports individually or together.